RESILIENSI DAN PERTUMBUHAN PASCA-TRAUMA PADA PENDERITA GAGAL GINJAL KRONIK DI HEMODIALISA 2023 : Resilience And Post-Traumatic Growth In Chronic Kidney Failure Patients Undergoing Hemodialysis In 2023 - Rosuli, Ahmad; Talita Anti Safitri; Hirdes Harlan; Diana Kusumawati; Rudiyanto (Institut Ilmu Kesehatan Nahdlatul Ulama Tuban, 2024)
Chronic kidney disease patients undergoing hemodialysis often face significant psychological challenges. Resilience, the ability to adapt and recover from difficulties, can influence post-traumatic growth in these patients. This study aims to identify the relationship between resilience and post-traumatic growth in chronic kidney disease patients in the hemodialysis unit of RSUD Blambangan in 2023. To determine the relationship between resilience and post-traumatic growth in chronic kidney disease patients undergoing hemodialysis therapy. This quantitative study used a cross-sectional approach. Data were collected through questionnaires distributed to 65 respondents undergoing hemodialysis therapy. Data analysis was performed using the Spearman test with the assistance of SPSS for Windows. The analysis results showed a significant relationship between resilience levels and post-traumatic growth in chronic kidney disease patients (ρ value = 0.001). Most respondents exhibited high resilience levels (58.5%) and moderate post-traumatic growth (96.9%). There is a positive relationship between resilience and post-traumatic growth in chronic kidney disease patients undergoing hemodialysis therapy. Higher resilience levels in patients are associated with a greater likelihood of experiencing post-traumatic growth. Keywords: Chronic Kidney Disease; Hemodialysi; Post-Traumatic Growth; Resilience.